Heidi Heckelbeck and the magic puppy - Coven, Wanda (Coven, Wanda. Heidi Heckelbeck, 2017)
Unable to find the owners of a lost puppy, Heidi decides to use just a teensy-weensy pinch of magic that sets off a mega-gigantic case of magic puppy trouble.